Tartu-Moscow Semiotic School and the Development of Semiotic Studies in Indonesia - Muzayin Nazaruddin (Asian Journal of Media and Communication, 2019)
This paper proposes the importance of the infusion of Tartu-Moscow Semiotics School (TMSS) into the development of semiotic studies in Indonesia. Semiotic studies in Indonesia have mostly departed from the ideas of Peirce, Saussure, and Barthes, while TMSS has not been recognized by Indonesian scholars. The paper proposes two concepts of TMSS, namely ‘text’ and ‘semiosphere’, which would significantly enhance semiotic studies in Indonesia. Indonesian scholars usually regard text as a concrete artefact, causing overgeneralization that every artefact is text, as well as oversimplification that every text is concrete artefact. Semiotic studies in Indonesia tend to exclude text as the object study from its cultural context and to analyse it in its individuality. While, TMSS defines text based on its meaningfulness, authority, and cultural functions. Besides its function as message carrier, TMSS proposes three functions of text, namely creative, poetic, and memory functions. These functions are connection points between a text and its wider cultural and historical contexts and its dynamic aspects. Finally, the concept of semiosphere, an abstract model in which semiosis occurs and outside of which semiosis cannot exist, would drive a holism perspective, avoiding the tendency to analyse the discrete text in its individuality.Keywords: Tartu-Moscow Semiotic School; text; text function; semiosphere; sign system.